A history of the modern world : - Colton, Joel (McGraw-Hill, 1995)
This text is one of the most highly praised history texts ever published. It has been adopted at more than 1000 schools and has been translated into six languages. This is the only text conceived and written as a history of the modern world, not merely as a truncated Western Civilization text.